Studying the effects of depression among university students in Malaysia - Mohd Rahmatullah, Syihan Zahin; Shahrul, Muhammad Aqil; Itqan, Muhammad Dzarif; Ahmad, Nur Intan Syafinaz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Depression is a prevalent mental health disorder that knows no boundaries when it comes to age, gender, or socioeconomic status. It affects people from all walks of life, regardless of their background or achievements. University life can be a transformative period, marked by academic pressures, social transitions, and increased responsibilities. These factors, along with the challenges of adapting to a new environment and the potential separation from family and friends, can contribute to increased vulnerability to mental health issues, including depression among universities students. Narrowing the focus of the study to Malaysian university students offers an opportunity to delve deeper into the complexities surrounding depression within this specific population. By examining the prevalence, cultural factors, and impact on academic performance, researchers can contribute to the development of targeted interventions, policies, and support services that address the unique needs and challenges faced by Malaysian university students experiencing depression. Based on the finding, it shown that many student are struggling with mental health issue which effect their daily life activities. From the survey, it also concluded that students feel anxiety a lot of time in a month. This is due to the financial problem, family problem and also bundle of assignment. Therefore university should run a program that is more relax for students to join to distract them from depression and students also must learn to take care of their mental health in order to ensure better future.